The Anderson Collection : Two Decades of American Graphics 1967-1987 : Prints - Multiples - Monotypes - Works in Paper - Fryberger, Betsy G. (Stanford : Stanford University Museum of Art, 1987)
Albers ; Arneson ; Arnoldi ; Bartlett ; Borofsky ; Celmins ; Close ; Diebenkorn ; Dill ; Dine ; Estes ; Francis ; Frank ; Frankenthaler ; Gilhooly ; Goldyne ; Guston ; Heizer ; Hilger ; Hockney ; Johns ; Kelly ; Lichtenstein ; etc.
The Anderson Collection : Two Decades of American Graphics 1967-1987 : Prints - Multiples - Monotypes - Works in Paper, Stanford University Museum of Art, Stanford, California, September 29, 1987 - January 3, 1988
boek
Keywords: Amerika